Antitumor effect of focal adhesion kinase inhibitor PF562271 against human osteosarcoma in vitro and in vivo. Issue 7 (8th June 2017) - Hu, Chuanzhen; Chen, Xu; Wen, Junxiang; Gong, Liangzhi; Liu, Zhuochao; Wang, Jun; Liang, Jing; Hu, Fangqiong; Zhou, Qi; Wei, Li; Shen, Yuhui; Zhang, Weibin
Abstract : Focal adhesion kinase (FAK) overexpression is related to invasive and metastatic properties in different kinds of cancers. Target therapy by inhibiting FAK has achieved promising effect in some cancer treatments, but its effect in human osteosarcoma has not been well studied. In the present study, we analyzed the antitumor efficacy of PF562271, an FAK inhibitor, against osteosarcoma in vitro and in vivo . Phosphorylated FAK (Y397) was highly expressed in primary human osteosarcoma tumor samples and was associated with osteosarcoma prognosis and lung metastasis. PF562271 greatly suppressed proliferation and colony formation in human osteosarcoma cell lines. In addition, treatment of osteosarcoma cell lines with PF562271 induced apoptosis and downregulated the activity of the protein kinase B/mammalian target of rapamycin pathway. PF562271 also impaired the tube formation ability of endothelial cells in vitro . Finally, oral treatment with PF562271 in mice dramatically reduced tumor volume, weight, and angiogenesis of osteosarcoma xenografts in vivo . These results indicate that FAK inhibitor PF562271 can potentially be effectively used for the treatment of osteosarcoma. Abstract : p‐FAK (Y397) was highly expressed in primary human osteosarcoma tumor samples and was associated with osteosarcoma prognosis and lung metastasis.FAK inhibitor PF562271 inhibits osteosarcoma cell proliferation and survival as well as angiogenesis in vitro and in vivo . PF562271 can potentially be effectively used for the treatment of osteosarcoma.